Leptomeningeal metastasis from extracranial solid tumors - Dilip Harindran Vallathol; Vijay Maruti Patil; Vanita Noronha; Amit Joshi; Nandini Menon; Kumar Prabhash (Cancer Research, Statistics, and Treatment, 2020)
Background: Leptomeningeal metastasis (LM) is a dreaded complication associated with solid tumors which is increasing due to the advances in cancer-directed therapy. Proper diagnostic and treatment criteria are still not established for the handling of LM. This article aims to help outline a management plan for LM. Methods: A systematic review of the articles on LM and solid tumors was done in PubMed for the past 15 years and eligible articles were eligible articles were considered. The articles related to hematological malignancies and brain tumors were excluded. Results and Discussion: LM usually requires a strong suspicion based on the natural history of the disease and symptoms for diagnosis. Symptomatology, cerebrospinal fluid (CSF) examination, and magnetic resonance imaging aid in the diagnosis. The treatment involves a multimodal institution of intra-CSF therapy, systemic chemotherapy, craniospinal irradiation, and surgical interventions for relief of symptoms. The prognosis is usually poor despite treatment and expected survival is between 4 and 6 months. Conclusion: The different options for the treatment of LM should be discussed in a multidisciplinary clinic. The treatment must be decided based on the neurological and general health condition of the patient, previous lines of treatment, and the presence of other metastatic sites. The improvement of levels of evidence for the various therapeutic procedures for patients with LM requires dedicated trials.